Future Prospect and Challenges of Genome Editing for Genetically Improvement of Plants in Indonesia - Bambang Prasetya; Satya Nugroho (Scientific Research, New Technologies and Applications Vol. 3, 2024)
The ease of use, accuracy and efficiency of genome-editing tools have led to their broad adoption in research, as well as proof of concept applications in gene therapies involving non-reproductive (somatic) cells. Climate change now in the next 10 years still become a concern for most countries. The quantity and quality of land, particularly that which is available for crop production, are declining, which prompts several attempts to create suitable technology for genetic improvement using a biotechnology method. Genome editing is a new and quickly evolving technology for performing genetic change that is being explored extensively. Numerous studies have effectively used genome editing to modify an organism’s DNA in order to improve its genetic traits without leaving any sign of foreign genes in the finished goods. There are research reports concerning the development of climate-compatible crops, high productivity, high quality and specific traits for animals and fish, effective and specifically targeted biocatalytic processes by using microorganisms, health-promoting foodstuffs and environmentally friendly production using genome editing approach. Genome editing requires a genetic engineering process for editing the genome, however, the products obtained can have similarities with the results of natural mutations. The genome editing approach will be an important alternative for genetic improvement, which is different to the existing GMO technologies, which have already been developed for almost 30 years. Many assessments concluded that genome editing will catalyze important innovations in the bioeconomy. This paper will discuss the global trends of genome editing and the opportunities and challenges faced in Indonesia. Moreover, it will also discuss the roles of the existing regulations and how they adapt to respond to this new technology. The bioeconomy of Indonesia will be nurtured by the development of genome editing technology. To accelerate the implementation of genome editing, however, appropriate regulations are needed.